Metagenomic Next-Generation Sequencing in the Diagnosis of HHV-1 Reactivation in a Critically Ill COVID-19 Patient: A Case Report - Shi, Lei; Xia, Han; Moore, Matthew D.; Deng, Chao; Li, Na; Ren, Hui; Chen, Yunru; Liu, Jinfeng; Du, Fenjing; Zheng, Gezhi; Li, Jing; Han, Qunying; et al. (Frontiers in Medicine, 2021)
Background: Secondary infections pose tremendous challenges in Coronavirus disease 2019 (COVID-19) treatment and are associated with higher mortality rates. Clinicians face challenge of diagnosing virus infection because of the less effective definitive laboratory tests. Case presentation: A 66-year-old woman initially manifested fever and shortness of breath. With a positive detection of SARS-CoV-2, she was diagnosed critically ill COVID-19 and treated with antiviral therapy, ventilator and extracorporeal membrane oxygenation (ECMO). However, the patient deteriorated with fever, frequent cough and increased airway secretions after the condition was relatively stabled for a few days. sputum bacterial and fungal cultures and smears were negative, raising the possibility of a newly acquired infection, but with unknown origin. Using metagenomic next-generation sequencing, we identified a reactivation of latent human herpes virus type 1 (HHV-1) in the respiratory tract, blood and gastrointestinal tract, resulting in a worsened clinical course in a critically ill COVID-19 patient on extracorporeal membrane oxygenation. Anti-HHV-1 therapy guided by these sequencing results effectively decreased HHV-1 levels, and improved the patient’s clinical condition. After 49 days on ECMO and 67 days on the ventilator, the 66-year-old patient recovered and was discharged. Conclusions: This case report demonstrates the potential value of metagenomics for evidence-based treatment, and suggests that potential reactivation of secondary latent viruses should be considered in critically ill COVID-19 patients.